Exploration of Ethnomathematics in the Mandar Traditional House as A Source of Deep Learning Based Instruction in Schools - Nurul Fiqriyah; Andi Aras; Buhaerah Buhaerah; Muhammad Ahsan (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematics learning is often delivered through procedural approaches that make mathematical concepts abstract and disconnected from students' cultural experiences, limiting meaningful learning. Integrating ethnomathematics into the Deep Learning curriculum offers a contextual approach that connects mathematics with local culture to promote meaningful, mindful, and joyful learning. This study aimed to identify the ethnomathematical concepts embedded in the Mandar Traditional House (Boyang) and explore their potential for Deep Learning–based mathematics instruction. A qualitative ethnographic approach was employed using one key informant, A'ba Tammalele, a traditional leader purposively selected for his extensive knowledge of Mandar culture and traditional architecture. Data were collected through participant observation, semi-structured interviews, architectural measurements, and documentation using observation guidelines, interview protocols, documentation sheets, and ethnographic field notes. Data were analyzed using Spradley's ethnographic model, including domain, taxonomic, componential, and cultural theme analyses. The findings revealed mathematical concepts related to geometry, measurement, spatial orientation, numerical symbolism, and geometric transformations embedded in the architectural elements of the Mandar Traditional House. These concepts reflect the cultural values and local knowledge of the Mandar community and provide authentic contexts for mathematics learning. The novelty of this study lies in integrating ethnographic findings with mathematical modeling and transforming them into a framework for Deep Learning–based mathematics instruction, thereby supporting both conceptual understanding and the preservation of local cultural heritage.